Can public venture capital support sustainability in the social economy? Evidence from a social innovation fund. - Vanderhoven, Ellen; Steiner, Artur; Teasdale, Simon; Calò, Francesca (Journal of Business Venturing Insights, 2020)
The Social Innovation Fund (SIF) - funded by Scottish Government and the European Social Fund - adopts a ‘public venture capital’ model to support socially innovative organisations. This article critically explores the use of public venture capital programmes to fund and grow the social economy through the case study of Heavy Sound Community Interest Company. We conclude that, while SIF funding helped Heavy Sound to scale-up an effective intervention in the short term, further significant scaling might undermine the project’s success and long-term sustainability was not assured. We call for further research into the long-term consequences of public venture capital programmes coming to an end, including coordinated evaluation of the SIF.
Keywords: Réservé UdeM; Scaling-up; UK

Can public venture capital support sustainability in the social economy? Evidence from a social innovation fund. - Vanderhoven, Ellen; Steiner, Artur; Teasdale, Simon; Calò, Francesca (Journal of Business Venturing Insights, 2020)
The Social Innovation Fund (SIF) - funded by Scottish Government and the European Social Fund - adopts a ‘public venture capital’ model to support socially innovative organisations. This article critically explores the use of public venture capital programmes to fund and grow the social economy through the case study of Heavy Sound Community Interest Company. We conclude that, while SIF funding helped Heavy Sound to scale-up an effective intervention in the short term, further significant scaling might undermine the project’s success and long-term sustainability was not assured. We call for further research into the long-term consequences of public venture capital programmes coming to an end, including coordinated evaluation of the SIF.
Keywords: Réservé UdeM; Scaling-up; UK